Energy Efficient Seismic Wave Propagation Simulation on a Low-Power Manycore Processor - Castro, Márcio; Dupros, Fabrice; Francesquini, Emilio; Méhautk, Jean-François; Navaux, Philippe O. A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2014: Anais do XXVI International Symposium on Computer Architecture and High Performance Computing, 2014)
Large-scale simulation of seismic wave propagation is an active research topic. Its high demand for processing power makes it a good match for High Performance Computing (HPC). Although we have observed a steady increase on the processing capabilities of HPC platforms, their energy efficiency is still lacking behind. In this paper, we analyze the use of a low-power manycore processor, the MPPA-256, for seismic wave propagation simulations. First we look at its peculiar characteristics such as limited amount of on-chip memory and describe the intricate solution we brought forth to deal with this processor's idiosyncrasies. Next, we compare the performance and energy efficiency of seismic wave propagation on MPPA-256 to other commonplace platforms such as general-purpose processors and a GPU. Finally, we wrap up with the conclusion that, even if MPPA-256 presents an increased software development complexity, it can indeed be used as an energy efficient alternative to current HPC platforms, resulting in up to 71% and 81% less energy than a GPU and a general-purpose processor, respectively.